Final Analysis Results from the AGEHA Study: Emicizumab Prophylaxis for Acquired Hemophilia A with or without Immunosuppressive Therapy - Shima, Midori; Suzuki, Nobuaki; Nishikii, Hidekazu; Amano, Kagehiro; Ogawa, Yoshiyuki; Kobayashi, Ryota; Ozaki, Ryoto; Yoneyama, Koichiro; Mizuno, Narumi; Sakaida, Emiko; Saito, Makoto; Okamura, Takashi; Ito, Toshihiro; Hattori, Norimichi; Higasa, Satoshi; Seki, Yoshinobu; Nogami, Keiji (Thrombosis and Haemostasis, 2024)
Primary analysis of the phase III AGEHA study suggested a favorable benefit–risk profile for emicizumab prophylaxis in patients with acquired hemophilia A (PwAHA); however, only patients undergoing immunosuppressive therapy (IST; Cohort 1) were included.To present final analysis results of AGEHA, including data on IST-ineligible patients (Cohort 2) and on long-term prophylaxis with emicizumab.For patients in both Cohorts 1 and 2, emicizumab was administered subcutaneously at 6 mg/kg on Day 1, 3 mg/kg on Day 2, and 1.5 mg/kg once weekly from Day 8 onward.Twelve patients (Cohort 1) and two patients (Cohort 2) were enrolled. Duration of emicizumab treatment was 8 to 639 days (median: 44.5 days) in Cohort 1 and 64 and 450 days in Cohort 2. In both cohorts, no major bleeds were observed after initial emicizumab administration. Six patients started their first rehabilitation sessions during emicizumab treatment and no rehabilitation-related bleeds occurred. Twenty-three surgeries were performed under emicizumab prophylaxis and there were no bleeds related to surgeries. Although asymptomatic deep vein thrombosis was reported in one patient in the primary analysis, no other thrombotic events occurred thereafter. Two patients developed anti-emicizumab antibodies, one of whom showed accelerated emicizumab clearance. Tailored IST approaches (delayed initiation, no use, or reduced dose) were successfully executed in three patients undergoing emicizumab prophylaxis.These results suggest that emicizumab prophylaxis has a favorable benefit–risk profile in PwAHA regardless of eligibility for IST.
Keywords: Factor VIII deficiency, acquired; long-term care; immunosuppressive therapy; rehabilitation; surgery